Vegetation height estimation near power transmission poles via satellite stereo images using 3D depth estimation algorithms - Qayyum A.; Malik A.S.; Saad M.N.M.; Iqbal M.; Abdullah F.; Rahseed W.; Abdullah T.A.R.B.T.; Ramli A.Q. (International Society for Photogrammetry and Remote Sensing, 2023)
Dynamic programming; Electric lines; Electric utilities; Graph algorithms; Graphic methods; Poles; Power transmission; Remote sensing; Satellites; Stereo image processing; Transmissions; Vegetation; 3D depth approach; Graph cut; QuickBird satellite; Satellite sensors; Stereo matching; Outages